Sex, Slander, and Television: The Christian Gospel Mission in Taiwan After Netflix’s "In the Name of God" - Yowting, Shueng (The journal of CESNUR, 2025)
In 2023, Netflix launched in several countries, including Taiwan, the TV miniseries In the Name of God: A Holy Betrayal, exposing Korean “cults,” and focusing on Providence, also known as the Christian Gospel Mission. The movement’s leader had already served a ten-year jail term for sexual abuse, and after the Netflix series was sentenced again for similar crimes. Netflix’s series, however, portrayed not only the leader but the whole large Providence church as a group including either “brainwashed” gullible members or accomplices of the sexual abuse crimes. In Taiwan, where Providence had been especially successful, the consequences were extremely negative for the local members, including college students and professionals. While not having been personally accused of any crimes, they were discriminated in schools and workplaces, insulted on social media, and some lost their jobs. The situation was especially difficult for female members. The article discusses the impact of sensationalized portraits of “cults” by the media and its consequences even in a tolerant society such as Taiwan.